2021
DOI: 10.3389/fpubh.2021.643053
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices Associated With COVID-19 Among Healthcare Workers in Hospitals: A Cross-Sectional Study in Saudi Arabia

Abstract: Lack of knowledge among healthcare workers (HCWs) about infectious diseases leads to delayed diagnosis of new cases, spread of infection, and poor infection control practices. Therefore, HCWs based in hospitals must be equipped with good knowledge about the pathogen and disease to put up a robust fight against the virus. The aim of this study was to assess knowledge, attitude, and practices (KAP) of HCWs about coronavirus disease 2019 (COVID-19) at multiple public and private hospitals in Riyadh, Saudi Arabia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
44
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 32 publications
11
44
6
Order By: Relevance
“…In addition, the internal reliability for the KAP scales were acceptable with a Cronbach's α of 0.7, 0.6, and 0.8, respectively. Further details on the scale validity and scoring were presented in the study that was conducted by part of the team in Saudi Arabia (8).…”
Section: Questionnairementioning
confidence: 99%
“…In addition, the internal reliability for the KAP scales were acceptable with a Cronbach's α of 0.7, 0.6, and 0.8, respectively. Further details on the scale validity and scoring were presented in the study that was conducted by part of the team in Saudi Arabia (8).…”
Section: Questionnairementioning
confidence: 99%
“…Female healthcare workers were perceptually more sound. A previous survey of COVID-19 indicated that the perception of female healthcare workers was more adequate than that of male healthcare workers (Almohammed et al 2021 ). Moreover, Nebhinani and Saini revealed that female healthcare workers more strongly perceived NCD (non-communicable disease) related information (Nebhinani and Saini 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the overall perceptions level of mucormycosis was significantly associated with the healthcare workers' age, gender, marital status, profession, monthly income, marital status, job type, and FNF death due to COVID-19. Similarly, numerous studies were conducted previously to assess the healthcare workers' perception level in different communicable diseases emergencies (Gizaw et al 2015 ; Ejeh et al 2020 ; Wake 2020 ; Dil et al 2020 ; Almohammed et al 2021 ; Fetansa et al 2021 ; and Roupa et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While there is a growing body of research on aspects of COVID-19 related health literacy of the general population [4,15,16,22] or specific populations, e.g., migrants, children, students, or patients [8][9][10][11]13,[19][20][21]23], little is known about the COVID-19 related health literacy of healthcare professionals, such as physicians, nurses, or psychologists. Since 2020, many studies have investigated the knowledge, attitude, and behavior of healthcare professionals worldwide [24][25][26][27][28][29][30][31][32][33][34]. The results indicate a lack of adequate knowledge about COVID-19 in many cases (6-42%) [24,25,27,32].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2020, many studies have investigated the knowledge, attitude, and behavior of healthcare professionals worldwide [24][25][26][27][28][29][30][31][32][33][34]. The results indicate a lack of adequate knowledge about COVID-19 in many cases (6-42%) [24,25,27,32]. Healthcare professionals having a higher education were found to have better knowledge about COVID-19 [28,33,35].…”
Section: Introductionmentioning
confidence: 99%